GLOBAL GOVERNANCE, CHINESE-STYLE: THE CENTRAL ASIAN PROJECTS OF THE ASIAN INFRASTRUCTURE INVESTMENT BANK - SERIKKALIYEVA, Azhar; AMIRBEK, Aidarbek; TAZHIBAYEV, Rashid; BEISENBAYEV, Olzhas (CENTRAL ASIA AND THE CAUCASUS, 2019)
Global governance underlies the solution of vital problems throughout the world. How can government mechanisms at the national, regional, and global levels promote transformational approaches designed to achieve economic, social, and environmental sustainability? China’s rapid growth in the international arena and its increasing influence are unprecedented. The Belt and Road Initiative (BRI), launched by Chinese President Xi Jinping during his visits to Central and Southeast Asia, has proposed a new strategic vision for trade and investment flows based on a concept of communications embodied in the ancient Silk Road. The BRI has become a powerful platform for economic growth and regional cooperation. Meanwhile, the range of financial instruments available to developing countries has been expanding with the establishment of new intergovernmental institutions such as the Asian Infrastructure Investment Bank (AIIB). This new international financial institution reflects a key change in the architecture of global governance. An analysis of China’s contribution to the multilateral system shows its unprecedented growth and commitment to global governance, as written into the country’s 13th Five-Year Plan. The principles of the United Nations 2030 Agenda, in turn, provide an agreed and inclusive basis for working out an international political approach to sustainable development with a focus on development cooperation. Global governance offers opportunities for further implementation of the U.N. Sustainable Development Goals (SDGs). In this context, the BRI reflects China’s global role as a bridge builder. The BRI can make a contribution to global governance by suggesting an effective implementation mechanism so as to move towards a more balanced, multipolar, and multilateral international architecture. The BRI’s gradual multilateralism will enhance China’s legitimacy and prestige. If the BRI builds on the Sustainable Development Goals, this will enhance China’s impact and give it additional advantages. Success will depend on concrete actions at the global, regional, national, and subnational levels. In addition, the BRI could be a driver of sustainable development, an effective tool for achieving the SDGs. Acting in harmony with the SDGs, the BRI will be able to promote the common good of participating countries in all areas of development. In this endeavor, regional and multilateral political frameworks are an important step in providing real win-win opportunities.